Determinants of Economic Growth in Indonesia Error Correction Model (ECM) Approach - Al Bina; Hwihanus, Hwihanus; Riyadi, Slamet (Medan Resource Center, 2023)
This study was conducted to see the effect of foreign debt, savings, domestic loans and total production factors on gross domestic product in Indonesia in the long and short-term using the error correction model method. The results of simultaneous tests (F-tests) of all independent variables have an influence on the dependent variable. External debt partially in the short term has no effect on gross domestic product in Indonesia and in the long term has an effect. Savings partially in the short term has no effect on gross domestic product in Indonesia and in the long term it has an effect. Domestic loans partially in the short term and in the long term have no effect on gross domestic product in Indonesia. Total production factors partially in the short and long term negatively affect gross domestic product in Indonesia.